The Impact of Economic Development Administration Programs: Some Empirical Evidence - Martin, Randolph C.; Graham, Robert E. (The Review of Economics and Statistics, 1980)
Randolph C. Martin, Robert E. Graham, Jr., The Impact of Economic Development Administration Programs: Some Empirical Evidence, The Review of Economics and Statistics, Vol. 62, No. 1 (Feb., 1980), pp. 52-62